Legitimating Organizational Secrecy - Clarke, Nicholas; Higgs, Malcolm; Garavan, Thomas (Journal of business ethics, 2025)
This paper brings into focus the concept of organizational secrecy by senior managers in the context of a major strategic change program. Underpinned by legitimation theory and utilizing a narrative methodology and a longitudinal investigation, we draw upon data from 52 interviews with 13 senior managers conducted at 3 months intervals over the course of 12 months. Our findings reveal that senior managers utilized seven discursive legitimation strategies to justify keeping secret that the organization intended to downsize, and they used a different mix of legitimation strategies as the change process evolved. We labeled these discursive legitimation strategies as (1) Naturalization, (2) Rationalization, (3) Moralization, (4) Authorization, (5) Proceduralization, (6) Valorization, and (7) Demonization. Theoretically we bring a temporal perspective to understanding organizational secrecy and the central role that discursive legitimation plays. We show that the use of these discursive legitimation strategies are anchored to meta-narratives describing work practices and values associated with the organization’s culture. And that managers use discursive legitimation to manage the ethical implications of secrecy.